1992
DOI: 10.1111/j.1365-3091.1992.tb02125.x
|View full text |Cite
|
Sign up to set email alerts
|

How round is round? A new approach to the topic ‘roundness’by Fourier grain shape analysis

Abstract: Numerous methods for roundness measurement have been developed. None, however, has been generally accepted, because of conceptual and practical deficiencies. Modern image processing and Fourier grain shape analysis have eliminated the practical shortcomings, but the conceptual ones remained. Single, higher harmonics of the Fourier series, for example, fail to serve as reliable equivalents for roundness evaluation. The concept outlined in this paper recognizes three criteria for the evaluation of roundness. (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 24 publications
0
32
0
1
Order By: Relevance
“…Further discussion of conceptual and practical issues regarding particle roundness are provided by Diepenbroek et al (1992).…”
Section: Roundness or Angularity: Analytical And Visual Approachesmentioning
confidence: 99%
“…Further discussion of conceptual and practical issues regarding particle roundness are provided by Diepenbroek et al (1992).…”
Section: Roundness or Angularity: Analytical And Visual Approachesmentioning
confidence: 99%
“…Surface grain-size has also been measured using emulsion-based photography (Kellerhals and Bray, 1971;Adams, 1979;Ibbeken and Schleyer, 1986;Church et al, 1987;Rice and Church, 1998), through direct measurement at grid-selected positions on the image, or by counting visible grains and conversion to a mean grain-size via a calibration relation (Church et al, 1987;Rice, 1995). This approach can be extremely time-consuming due to the post processing required, with even the more advanced photo-sieving procedures requiring manual identification and digitisation of grain boundaries (Ibbeken and Schleyer, 1986;Diepenbrook et al, 1992;Diepenbrook and De Jong, 1994;Ibbeken et al, 1998). More recently, digital imagery and automated image processing techniques have been introduced, that provide accurate representations of grain roughness but are limited to small areas (Butler et al, 1998(Butler et al, , 2001aLane, 2002, Sime andFerguson, 2003;Graham et al, 2005), with the exception of Carbonneau et al (2004Carbonneau et al ( , 2005) who have demonstrated some success in the use of aerial imagery for grain-size determination over larger areas of river channel.…”
Section: Introductionmentioning
confidence: 99%
“…However, such a method merely compares visual images, and therefore, the derived roundness values are not strictly quantitative. The second approach involves the quantitative determination of various shape parameters, and many evaluation methods have been designed to obtain relevant shape parameters (e.g., Schwarcz and Shane 1969;Orford and Whalley 1983;Diepenbroek et al 1992;Yoshimura and Ogawa 1993;Vallejo and Zhou 1995;Bowman et al 2001;Itabashi et al 2004;Drevin 2007;Blott and Pye 2008;Lira and Pina 2009;Roussillon et al 2009;Arasan et al 2011;Suzuki et al 2013Suzuki et al , 2015. Both approaches, however, involve the analysis of each individual particle, and therefore, production of several thousand to several tens of thousands of shape parameters for reliable analysis is time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies into particle shape have been discussed in a series of review articles (e.g., Barrett 1980;Clark 1981;Winkelmolen 1982;Diepenbroek et al 1992;Blott and Pye 2008), and in general, such studies have mainly taken one of two approaches to understanding particle shape. The first is a simple method that involves the examination of visual images of particle grains (e.g., Krumbein 1941;Rittenhouse 1943;Powers 1953;Pettijohn 1957;Lees 1963).…”
Section: Introductionmentioning
confidence: 99%